A computer-oriented iterative design of linear control systems subject to open-and closed-loop specifications - Zaborszky, J.; Marsh, R. G. (Transactions of the American Institute of Electrical Engineers. Part 2, Applications and industry, 1962)
An iterative technique is introduced which can be used to design on the digital computer a linear control system satisfying a set of performance specifications such as overshoot, peak time, settling time, velocity constant, bandwidth, etc., and incorporate a plant with a specified transfer function. The design is flexible in the number and nature of constraints used. It is nearly completely mechanical, demanding only one rough initial estimate from the designer.